Changes in prothrombin and activated partial thromboplastin time during replacement therapy with human recombinant growth hormone in growth hormone deficient adults - Miljic, Dragana; Miljic, Predrag; Doknic, Mirjana; Pekic, Sandra; Djurovic, Marina; Colovic, Milica; Popovic, Vera (Hormones (Athens, Greece), 2006)
In rodents, Growth Hormone (GH) has been shown to stimulate coagulation parameters, including Prothrombin Time (PT), activated Partial Thromboplastin Time (aPTT) and vitamin K dependent coagulation factors. However, there are no reports on the influence of GH replacement therapy on global coagulation tests in Growth Hormone Deficiency (GHD). The aim of this study was to investigate the effects of GH administration on basic coagulation parameters: PT, aPTT and fibrinogen concentrations in adult GHD patients before and during one year of GH replacement. Twenty-one adult patients with severe GHD (mean age +/- SE: 38.6 +/- 2.8 years) were included in this hospital based, prospective, interventional study. All patients were treated with rhGH for 12 months (GH dose: 0.4 mg/day for male and 0.6 mg/day for female patients). IGF-1 concentrations were determined using RIA-INEP kits. Basic coagulation tests, i.e. aPTT and fibrinogen concentrations, were measured before and after 3, 6 and 12 months of treatment with rhGH. Control values were obtained from fourteen "healthy" subjects matched by age, sex and body mass index (BMI). At baseline, we observed no significant differences in PT, aPTT and fibrinogen values between GHD and healthy subjects. IGF-1 concentrations increased significantly within 3 months of GH therapy (8.2 +/- 1.5 vs. 24.2 +/- 2.9 nmol/l, p <0.05) and remained stable thereafter. A significant increase in PT values, which was more pronounced in female subjects, was noted after 6 and 12 months of treatment with GH. aPTT values increased significantly after 12 months of treatment only in male patients (28.8 +/- 4.6 vs. 39.7 +/- 2.1 s.; p <0.05). No significant changes in fibrinogen concentrations were found during the study. Twelve months of GH replacement therapy led to a significant increase in PT and aPTT values in adult GHD patients, while fibrinogen concentrations did not change. Changes in PT were more pronounced in female GHD patients, while an increase in aPTT values was observed only in male patients with GHD. The clinical significance of these changes needs further evaluation.